Methodic of pedagogic control of 16-17 years' age girls' motor fitness - O.V. Ivashchenko (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Increase of schoolchildren's motor fitness is connected with organization of pedagogic control at physical culture lessons. It was assumed that the basis for pedagogic control of 16-17 years' age girls' motor fitness was discriminant model. Purpose: to determine methodological approaches to pedagogic control of 16-17 years' age girls' motor fitness. Material: in the research 28 senior form girls (fourteen 16 years' age 14 girls of 17 years' age girls) participated. Materials of the research were processed in statistical analysis program- IBM SPSS 20. Results: in the process of discriminant analysis we created prognostic model for belonging to group. This model builds discriminant function in the form of linear combination of predicting variables, which ensures the best division of groups. Correlation coefficient between calculated values of discriminant function and indicators of belonging to group was r =0.843 and witnesses about high prognostic potential of first canonic function. Conclusions: 16 years' age girls have better speed-power fitness than 17 years' girls. It points at the fact that in 17th years' age the reason of lagging behind 16 years' age girls is their insufficient motor activity. On the base of canonic coefficients of discriminant function it is possible to classify 16 and 17 years' age girls by level of their motor fitness, according to their age. It is of practical importance for working out effective programs of senior form girls' physical training. Discriminant model can be used for pedagogic control of 16 and 17 years' age girls' fitness.